Moral education in the context of the arts - Caldarera, Joan (Frontiers in Education, 2025)
This paper describes a moral education arising from artistic choices and problem solving from out of one’s soul, which lead to a way of taking interest in the world and to being flexible in one’s views. Making choices creatively, imaginatively becomes a habit through a truly artistic education. So does maintaining an inner confidence Through Waldorf education, students choose to nourish their soul; to hold themselves accountable; to have the freedom to realize knowledge from risk and failure; and to experience thinking not just in their heads, but also in their hands or bodies, depending on the medium. To be able to accomplish all this integration of experiences through the creative process and offer something beautiful back to the world is proof enough of their innate wisdom This paper examines the role of imagination and the arts that rely on imagination as catalysts for moral intelligence. From there, a discussion on the place of morality in educating for a democratic people and as a goal of Waldorf education in general is examined.